2002
DOI: 10.1029/2000wr000197
|View full text |Cite
|
Sign up to set email alerts
|

Geologic and hydrologic controls on the movement of water through a thick, heterogeneous unsaturated zone underlying an intermittent stream in the western Mojave Desert, southern California

Abstract: [1] A two-dimensional, axially symmetric, unsaturated flow model was developed to test hypotheses about geologic and hydrologic controls on the movement of water through the thick, heterogeneous, unsaturated zone underlying Oro Grande Wash in the Mojave Desert, California. Heterogeneity within the unsaturated zone was simulated with multiple realizations of subsurface geology estimated on the basis of transition probability/Markov chain statistics. Model results show lateral spreading of water away from the wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 34 publications
1
44
0
Order By: Relevance
“…Although, the areal extent of tritium in these areas is small in comparison with the areal extent of tritium in the floodplain aquifer along the Mojave River, these data indicate areas of recent ground-water recharge along the mountain front and support recharge to the steady-state model in this area. Although, tritium was not present in water from wells in the regional aquifer near Cajon Pass, studies of infiltration from intermittent streams in this area show that small amounts of recharge occur in this area under present-day climatic conditions (Izbicki, 2002;Izbicki et al, 1998Izbicki et al, , 2000Izbicki et al, , 2002.…”
Section: Tritium and Carbon-14 Datamentioning
confidence: 93%
“…Although, the areal extent of tritium in these areas is small in comparison with the areal extent of tritium in the floodplain aquifer along the Mojave River, these data indicate areas of recent ground-water recharge along the mountain front and support recharge to the steady-state model in this area. Although, tritium was not present in water from wells in the regional aquifer near Cajon Pass, studies of infiltration from intermittent streams in this area show that small amounts of recharge occur in this area under present-day climatic conditions (Izbicki, 2002;Izbicki et al, 1998Izbicki et al, , 2000Izbicki et al, , 2002.…”
Section: Tritium and Carbon-14 Datamentioning
confidence: 93%
“…Direct disturbance to intermittent and ephemeral waters would result from site grading and from modifying flow pathways to avoid the erosion of facility infrastructure. Consequently, significant changes in surface water flow could affect the transport of sediment, nutrients, minerals, and organic matter that maintains habitat and geomorphological processes in downstream reaches (Webb et al 2000;Izbicki 2002Izbicki , 2007Larned et al 2010;Smith et al 2011). Although species in arid environments are generally adapted to temporary drying, the abundance and composition of animal communities would be altered in streams experiencing significant changes in the timing, duration, velocity, and magnitude of surface flow (Stanley et al 1994;Lake 2003;Sada et al 2005;Archer and Predick 2008;McCluney and Sabo 2011;Datry 2012).…”
Section: Construction Phasementioning
confidence: 98%
“…As in humid climates, a primary function of water bodies in desert regions is to provide physical and biological connectivity across the landscape. Intermittent and ephemeral streams transport water originating from upland snowmelt and precipitation to downstream perennial reaches, thereby maintaining flow and recharging groundwater (Izbicki 2002;Larned et al 2010;Smith et al 2011). In addition to hydrologic connectivity, the downstream transport of sediment, nutrients, minerals, and organic matter is a critical function of intermittent and ephemeral streams (Larned et al 2010).…”
Section: Introductionmentioning
confidence: 98%
“…Using a stochastic approach, Yeh et al (1985a,b,c) and Mantoglou and Gelhar (1987) have shown that soil heterogeneity can significantly affect the spatial distribution of pressure head and water content, causing great lateral spreading of water under steady or transient infiltration in the vadose zone. While areal variation in soil heterogeneity affects areal variation in the infiltration process, vertical variations (such as stratification) retard rainfall infiltration, cause great lateral migration of infiltrating water, and in turn, enhance evaporatranspiration while reducing groundwater recharge (Izbicki, 2002). To model these processes in detail, a three-dimensional model for the vadose zone processes is imperative.…”
Section: Introductionmentioning
confidence: 99%